UPAYA HUKUM PENYELESAIAN SENGKETA ASET KREDIT AKIBAT (CESSIE) SETELAH PELELANGAN OLEH BADAN PENYEHATAN PERBANKAN NASIONAL YANG BERKEADILAN (Lex Jurnalica, 2021)
AbstractJustice in court decisions not only accommodates the rules that apply at the most social stage of finding justice, nor is it just a juridical issue, but also a legal culture problem in society. The character of substantive justice which is based on the public opinion, is able to recognize the public's wishes and is committed. In practice, the judge's decision regarding the settlement of the problem with the National Bank Restructuring Agency (IBRA) is not accepted by the public because there is no legal certainty and protection for the community and the judge's decision is still subject to power intervention and various political interests. Problems after IBRA liquidated the collateral for Credit Assets Consequences (Cessie) of the syndicated 7 bankrupt banks owned by PT GWP through the auction of the Credit Asset Sales Program (PPAK) VI in 2004, which resulted in disputes between individuals and other parties. The type of research is empirical normative legal and the achievement of truth based on the philosophical paradigm of law, by applying a socio-legal approach critically, interpretively or constructively, then the research motive is (1) to explore (2) to criticize (3) to understand the hidden meanings behind the object or subject to be focus studied and research the answer the problematic phenomena. The point of view of legal theories to find answers the problems regarding legal culture and legal remedies for settlement justice in the Court of Cassation by the Supreme Court, will impact in society become a challenging deep investigation. Keywords: IBRA, justice, Cessie AbstrakKeadilan pada Putusan pengadilan tidak hanya mengakomodir aturan yang berlaku pada tahapan penemuan keadilan yang paling sosial, juga bukan hanya persoalan yuridis semata, akan tetapi masalah budaya hukum dalam masyarakat. Karakter keadilan yang bertumpu pada respon masyarakat, mampu mengenali keinginan publik dan berkomitmen. Pada prakteknya putusan hakim menyangkut penyelesaian masalah BPPN tidak diterima masyarakat karena tidak ada kepastian dan perlindungan hukum bagi masyarakat juga masih ada intervensi kekuasaan dan berbagai kepentingan politik. Problematika setelah BPPN melikuidasi jaminan Aset Kredit Akibat (Cessie) sindikasi 7 bank pailit milik PT GWP melalui pelelangan PPAK VI tahun 2004, berujung pada persengketaan individu dan pihak-pihak lainnya. Jenis penelitian adalah penelitian hukum normatif empiris dan pencapaian kebenaran berdasarkan pada paradigma filosofis hukum, dengan menerapkan pendekatan socio-legal secara kritis, interpretatif atau konstruktivis, maka motif penelitian adalah untuk (1) to explore (2) to critizise (3) to understand diharapkan dapat ditemukan makna-makna yang tersembunyi di balik objek maupun subjek yang akan diteliti dan menjawab fenomena problematika yang menjadi fokus studi penelitian ini. Permasalahan mengenai budaya hukum dan upaya hukum penyelesaian pada pengadilan Kasasi oleh putusan Mahkamah Agung yang berkeadilan dari sudut pandang teori-teori hukum untuk mencari jawaban atas implikasi sosial, moral dan filosofis di masyarakat menjadi tantangan penting untuk diteliti lebih mendalam.  Kata Kunci : Badan Penyehatan Perbankan Nasional, Keadilan, Cessie